PEMBERDAYAAN UMKM: PELATIHAN DESAIN KEMASAN BAGI UKM ANEKA KERIPIK AIDAA DESA ARJASA, KABUPATEN JEMBER - Fawait Afnani; A. Sirojul Anam Izza Rosyadi; Putri Satika Dewi; Putu Tessa Fadhila; Ade Galuh Rakhmadevi; Rasmiyana Rasmiyana (Universitas Negeri Makassar, 2026)
A packaging design training using Canva was conducted to empower MSMEs, specifically Aneka Keripik Aidaa in Arjasa Village, Jember Regency, by enhancing partners’ visual marketing and digital literacy. The main problem faced by SMEs (small-medium enterprises) Aneka Keripik Aidaa in Arjasa Village, Jember, is traditional product packaging that does not meet modern marketing standards, hindering competitiveness and brand identity. This community service activity aims to empower partners through product packaging design training based on digital technology using the Canva application. The implementation method was carried out through problem screening stages, field observations, brainstorming, technical training, design simulation assistance, and evaluation using pre-test and post-test of questionnaires. The results showed the success of redesigning banana chip product packaging to be more informative, aesthetic, and compliant with food labeling standards. Quantitative evaluation showed a significant increase in participant knowledge (p < 0.05) based on the Paired t-test analysis, with an increase in the average score from 24.0 (pre-test) to 39.0 (post-test). Regarding knowledge demographics, there was a shift from the dominant medium category (86%) to the high category (71%) after training. In conclusion, the training enhanced partners’ digital literacy and visual marketing, strengthening branding and market reach.